PERBEDAAN ASUPAN MAKANAN PADA AKHIR PUASA RAMADHAN DENGAN SATU MINGGU, DUA MINGGU DAN TIGA MINGGU SETELAH IDUL FITRI PADA KOMPI VI TANK BANDUNG - Lola Ilona; Setiawan Setiawan; Gaga Irawan Nugraha; Titing Nurhayati (JURNAL ILMU FAAL OLAHRAGA INDONESIA, 2018)
Indonesia's Muslim society is obligated to carry out the fast of Ramadan. In general, the Muslims carrying out fasting Ramadan are likely to consume foods that are high in fat, protein, and carbohydrate although the frequency and amount of eating food intake decrease. The habit of eating foods wide high in fat, protein, and carbohydrate maintained until after the Eid al-Fitr. This research aims to know the differences in energy intake comes from carbohydrates, protein, and fat between the end of the Ramadan fasting (25/9/2008) and the time of Eid al-Fitr, 1 week(6/10/2008), 1 week (15/10/2008), 1 week (24/10/2008) after the Eid al-Fitr. The subject is a member company of Yonkav (cavalry battalion) 4 Tanks of Bandung, randomly selected, aged 20-29 years, already carry out month-long fast of Ramadan and in a healthy condition. The type of this research is a descriptive longitudinal. Food intake at the end of the fast of Ramadan (25/9/2008), 1 week (6/10/2008), 1 week (15/10/2008), 1 week (24/10/2008) after the Eid al-Fitr is recorded using the 24-hour recall. The data obtained are then processed to obtain data regarding the percentage of total energy intake, the intake of energy comes from carbohydrates, proteins, and fats. The results showed a rise in total energy intake and energy intake comes from fat also decrease intake of energy comes from carbohydrates on Idul Fitri, 1 week, 2 weeks, 3 weeks after Idul Fitri as compared to the end of the fasting of Ramadan. While the intake of energy derivedfrom protein has no change.